Community customs law : a guide to the customs rules on trade between the (enlarged) EU and third countries : with value added tax upon importation and exportation /: a guide to the customs rules on trade between the (enlarged) EU and third countries : with value added tax upon importation and exportation. (1995) - Unknown
No abstract available